Pd/Fe3O4 supported on nitrogen-doped reduced graphene oxide for room-temperature isocyanide insertion reactions12. Issue 11 (19th May 2016) - Singh, Karandeep; Singh, Ajay K.; Singh, Devendra; Singh, Rakhi; Sharma, Siddharth
Abstract : A versatile Pd/Fe3 O4 supported on N-doped reduced graphene oxide (N-rGO) catalyst was developed to carry out the synthesis of quinazolinones and phenanthridines under extremely mild conditions through isocyanide insertion cascades. Abstract : A versatile Pd/Fe3 O4 supported on N-doped reduced graphene oxide (N-rGO) catalyst was developed to carry out the synthesis of quinazolinones and phenanthridines under extremely mild conditions through isocyanide insertion cascades. The supported Pd/Fe3 O4 nanoparticles could be easily recovered from the reaction mixture and reused several times without any loss in catalytic activity.